2009
DOI: 10.1021/jp908821b
|View full text |Cite
|
Sign up to set email alerts
|

1,6-Hexanedithiol Self-Assembled Monolayers on Au(111) Investigated by Electrochemical, Spectroscopic, and Molecular Mechanics Methods

Abstract: 1,6-Hexanedithiol (HSC 6 SH) self-assembled monolayers (SAMs) on Au(111) were formed in a 1 mM ethanolic solution and were investigated by voltammetry in 0.1 M aqueous KOH solution. HSC 6 SH SAMs on Au(111) were further probed by X-ray photoelectron spectroscopy (XPS), scanning tunneling microscopy (STM), sum frequency generation spectroscopy (SFG), and molecular mechanics calculation (MMC). An identical investigation was performed with the self-assembly of hexanethiol (C 6 SH) on Au(111) for comparison. Linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 85 publications
0
36
0
Order By: Relevance
“…13 Shown in Figure 2A is the cyclic voltammogram for the reductive desorption of dodecanethiol (DT) adsorbed on flat Au surfaces, where a main desorption wave is observed at -1.06 V. This desorption peak potential is close to that previously reported for DT monolayers on Au surfaces. 8,13,14 The origin of a satellite desorption wave observed at -0.92 V can be ascribed to the difference in the microscopic roughness on the Au substrates used in this study. 15 The total charge associated with the reductive desorption of DT on flat Au surfaces is estimated to be ca.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…13 Shown in Figure 2A is the cyclic voltammogram for the reductive desorption of dodecanethiol (DT) adsorbed on flat Au surfaces, where a main desorption wave is observed at -1.06 V. This desorption peak potential is close to that previously reported for DT monolayers on Au surfaces. 8,13,14 The origin of a satellite desorption wave observed at -0.92 V can be ascribed to the difference in the microscopic roughness on the Au substrates used in this study. 15 The total charge associated with the reductive desorption of DT on flat Au surfaces is estimated to be ca.…”
mentioning
confidence: 79%
“…This corresponds to the charge density of 110 µC cm -2 , which is slightly larger than that observed for alkanethiol SAMs with a monolayer coverage of (√3 × √3) R30 o structures on Au(111) surfaces. 14 On NPG surfaces, the reductive peak potential of DT monolayers nega-…”
mentioning
confidence: 99%
“…[38][39][40][41][42] In addition, it was found that reductive desorption peaks for COOH-terminated alkanethiol SAMs on Au electrodes appeared at less negative potential compared to the corresponding CH 3 -terminated alkanethiol SAMs, 42 and fluorinated aromatic thiol SAMs on Ag electrodes showed similar reductive desorption behavior to the corresponding hydrogenated aromatic thiol SAMs. 43 These results imply that the reductive desorption for organic thiol SAMs on metal electrodes occurs more easily when the organic thiols contain electron withdrawing groups, since such groups act as good electron acceptors in the reduction process.…”
Section: R-s-mentioning
confidence: 99%
“…To understand these fundamental issues, STM has been used as one of the very powerful tools for visualizing the atomic-and molecular-scale surface structures of SAMs on metal surfaces, as demonstrated in many previous reports. [1][2][3][4][6][7][8][9][10][11][12][13][14][15][16][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Additionally, thermal desorption spectroscopy (TDS) 10,11,32,[34][35][36][37] and electrochemical measurements [38][39][40][41][42][43] are very useful techniques to investigate the adsorption conditions, thermal stability, and the electrochemical behavior and stability of SAMs. TDS measurements revealed that alkanethiol SAMs exist as a form of monomer (alkanethiolate), not dimers (dialkyl disulfides) derived from associa-tive reactions of the sulfur headgroups, 10,11,34,…”
mentioning
confidence: 99%
See 1 more Smart Citation